Surface chemistry and adsorption mechanism of cadmium ion on activated carbon derived from Garcinia mangostana shell - Kang, Y.L.; Poon, M.Y.; Monash, P.; Ibrahim, S.; Saravanan, P. (2013)
A detailed surface characterizations and adsorption mechanism of Cd2+ on chemical activated carbon (CAC) prepared from Garnicia mangostana shell were investigated. The activation is accomplished in self-generating atmosphere using phosphoric acid as activating agent. The characterizations performed are elemental analysis, functional group identification, N2 adsorption isotherm and surface charges. Adsorption mechanism of metal ion was tested using Cd2+ as model ion. CAC achieved BET surface area of 1,498 m2/g with a mixture of micro and mesopores. The point of zero charge is observed to be at pH 2.8 and the optimum pH for Cd2+ adsorption on CAC is 12. The adsorption isotherm followed the Freundlich model, and the adsorption kinetics was explained by pseudo-second order kinetic model. From thermodynamic studies, the adsorption was found to be physical adsorption. X-ray photoelectron spectroscopy (XPS) confirmed the adsorption of Cd2+ onto CAC as +2 oxidation state. Â© 2013 Korean Institute of Chemical Engineers, Seoul, Korea.